Examining Risk Management and Risk Disclosures Practices in UK Public Companies - Jiang, Nan (2008)
Although the concepts of risk and risk management are not new in literature and managerial practice, it has only draw considerable attention recently. Linsley and Shrives (2006) suggest, "these attention has yet to be reflected in empirical research examining firms' risk reporting practices". This dissertation examines and discusses risk management and risk disclosures practices of fifteen UK listed companies from three different industries, over a period of five years from financial year 2003 to 2007. The purpose of this dissertation is to find out how has companies' risk management and risk disclosures practices changed over the analysis period. Following a content analysis, the results show companies' overall performance on risk management and risk disclosure practices have significantly improved during the five years. However, only a few companies in this study have appointed a CRO or a risk committee to oversee companies' risk management system. More interestingly, this information is not well reflected in their public reports. In term of the volume of risk disclosures, the result shows a trend of steady increase during the five-year period. There is evidence suggest the volume of risk disclosures is positively correlated with company size, but no relationship was found between industry and the volume of risk disclosures. The result also shows companies' size and the appointment of CRO affect their performance on risk management and risk disclosures practices. In testing the disclosures of methods for risk quantification, only 4 out of 15 companies have reported what are the methods that they employed to quantify risk exposures, and most companies stress on quantifying financial risks. Overall, the results demonstrate that companies' reports are still incomplete and need to be improved.